2023
DOI: 10.1101/2023.03.10.532103
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of daylength sensitivity by splice site mutation in Cannabis

Abstract: Adaptations to high latitude photoperiods have been under positive selection during the domestication of many short-day (SD) flowering crops. Photoperiod insensitivity (auto-flowering) in drug-type Cannabis sativa circumvents the need for SD flowering requirements making outdoor cultivation in high latitudes possible. However, the benefits of photoperiod insensitivity are counterbalanced by low cannabinoid contents and poor flower quality in auto-flowering genotypes. Despite recent legalization in some countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Indeed, the 17 instances of this inversion were found to be heterozygous in 15 samples and homozygous in one. This inverted region contains 1,203 genes, spanning many functions, including the core circadian and flowering time gene PSEUDO RESPONSE REGULATOR 3 ( PRR3 ) implicated in the DN behavior of “autoflower” cannabis 21,26,58 , but are significantly enriched for catalytic activity, transport activity, and binding gene ontology (GO) categories. Pairwise SNP r 2 values and local PCA plots of this area suggest some level of haplotype formation and elevated linkage disequilibrium (LD) across this region, especially at the interior breakpoint (Supplemental Fig.…”
Section: Mainmentioning
confidence: 99%
“…Indeed, the 17 instances of this inversion were found to be heterozygous in 15 samples and homozygous in one. This inverted region contains 1,203 genes, spanning many functions, including the core circadian and flowering time gene PSEUDO RESPONSE REGULATOR 3 ( PRR3 ) implicated in the DN behavior of “autoflower” cannabis 21,26,58 , but are significantly enriched for catalytic activity, transport activity, and binding gene ontology (GO) categories. Pairwise SNP r 2 values and local PCA plots of this area suggest some level of haplotype formation and elevated linkage disequilibrium (LD) across this region, especially at the interior breakpoint (Supplemental Fig.…”
Section: Mainmentioning
confidence: 99%
“…Two recent mapping studies have suggested C. sativa homologs of APETALA2 and PSEUDO-RESPONSE REGULATOR 37 (PRR37) as candidate genes within Autoflower1 (Garfinkel et al, 2023;Leckie et 2023). Alterations of PRR37 homologs in T. aestivum, O. sativa and Sorghum bicolor are known to confer photoperiod insensitivity due to de-repressed FT expression (Beales et al, 2007;Koo et al, 2013;Murphy et al, 2011).…”
Section: Photoperiod Insensitivity Originated Multiple Times Independ...mentioning
confidence: 99%
“…in cannabis, and it has been shown that a mutation of that gene is correlated with the autoflowering trait, or lack of response to photoperiod 12 . GHD7 has also been implicated as a predictor of yield in rice 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis CONSTANS-like genes have been identified, and in fact there are at least 13 expressed CONSTANS-like genes 15 . In cannabis, florigen-like, PRR37-like, and SOC1-like genes have also been identified 12,16 . In this paper, we present experimental data which characterizes the expression patterns of these genes, their responsiveness to phytochrome via manipulation of the ratio of red to far red light, and the resulting impact on phenotype and chemotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation